2013
DOI: 10.1177/1350650113499555
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication of a flexible piston skirt conjunction subjected to thermo-elastic deformation: A combined numerical and experimental investigation

Abstract: The piston-cylinder conjunction accounts for nearly 50% of all the parasitic frictional losses in an IC engine of which the piston skirt accounts for nearly half of these losses. Consequently, part-circumferential short skirted compliant pistons have become a development trend, particularly for high-performance engines. Another trend has been the use of light weight moving parts to reduce inertial imbalance. This has led to the use of shorter lighter pistons constructed from lower density materials, such as al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
(43 reference statements)
0
23
0
Order By: Relevance
“…They have all combined the oil film behaviour with piston dynamics (tribo-dynamics), forming a multi-physics study of the piston's secondary motion. Further studies have been reported with the variations in the lubrication regime during the full engine cycle taken into account, together with the piston-profile and the connecting rod effects [6,8,[23][24][25]. The above mentioned piston-liner contact tribo-dynamic models are employed to identify piston slap events, irrespective of the structural excitation, engine block response and sound quality (dB levels and frequency) perceived by the receiver [26].…”
Section: List Of Symbolsmentioning
confidence: 99%
“…They have all combined the oil film behaviour with piston dynamics (tribo-dynamics), forming a multi-physics study of the piston's secondary motion. Further studies have been reported with the variations in the lubrication regime during the full engine cycle taken into account, together with the piston-profile and the connecting rod effects [6,8,[23][24][25]. The above mentioned piston-liner contact tribo-dynamic models are employed to identify piston slap events, irrespective of the structural excitation, engine block response and sound quality (dB levels and frequency) perceived by the receiver [26].…”
Section: List Of Symbolsmentioning
confidence: 99%
“…These are particularly important practical features of low rotational inertia high-performance race engines, subject of the current paper. After some manipulation and accounting for the effect of engine order vibrations [2,33] and Littlefair et al [19], the kinematic displacement, velocity and acceleration are obtained as (''Appendix 1'' for A and B coefficients):…”
Section: Dynamic and Kinematic Analysismentioning
confidence: 99%
“…The methodology used for the estimation of the piston's deflection is the same as that presented by Littlefair et al [19]. However, for completeness, a brief summary is provided here.…”
Section: Deformation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The deformation of the bore and ring can originate from thermal and mechanical loading, cylinder head bolt tightening and abrasion [10][11][12]. In practice, the bore is not a right circular cylinder, which affects the ring-bore conjunctional friction and gas flow [13].…”
Section: Introductionmentioning
confidence: 99%